1992
DOI: 10.1172/jci115905
|View full text |Cite
|
Sign up to set email alerts
|

Fat-storing cells as liver-specific pericytes. Spatial dynamics of agonist-stimulated intracellular calcium transients.

Abstract: Liver perisinusoidal fat-storing cells (FSC) show morphological and ultrastructural characteristics similar to pericytes regulating local blood flow in other organs. In the present study we have analyzed whether FSC respond to local vasoconstrictors such as thrombin, angiotensin-II, and endothelin-1 with an increase in intracellular free calcium concentration (ICa2I1I) coupled with effective cell contraction. All agonists tested induced a rapid and dose-dependent increase in ICa2`i1 followed by a sustained pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
199
1
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 315 publications
(208 citation statements)
references
References 23 publications
6
199
1
2
Order By: Relevance
“…Recent investigation found that voltage-operated calcium channel (VOCC) plays an important role in the regulation of hepatic stellate cells contractility which is the marked phenotype of activated hepatic stellate cells (Berlin 1995;Bataller et al 1998). Moreover, activated hepatic stellate cells have receptors for a number of vasoconstrictor substances such as endotheline, angiotensin II, vasopressin, thrombin and thromboxan A2 (Pinzani et al 1992;Sakamoto et al 1993;Kawada et al 1993;Bataller et al 1997;Rockey 1997). Therefore, it is likely that the inhibitory effect of tetrandrine on hepatic stellate cells activation, at least in part, through the blocking of calcium channels.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigation found that voltage-operated calcium channel (VOCC) plays an important role in the regulation of hepatic stellate cells contractility which is the marked phenotype of activated hepatic stellate cells (Berlin 1995;Bataller et al 1998). Moreover, activated hepatic stellate cells have receptors for a number of vasoconstrictor substances such as endotheline, angiotensin II, vasopressin, thrombin and thromboxan A2 (Pinzani et al 1992;Sakamoto et al 1993;Kawada et al 1993;Bataller et al 1997;Rockey 1997). Therefore, it is likely that the inhibitory effect of tetrandrine on hepatic stellate cells activation, at least in part, through the blocking of calcium channels.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In their activated phenotype, stellate cells are characterized by remarkable proliferative, chemotactic, and contractile properties. Particularly, contraction of activated HSCs in response to different vasoconstrictors, including endothelin 1 and thrombin, 8,13,14 has been suggested to play an important role in the contraction of developing scar tissue, and, consequently, in the progression of portal hypertension. HSC contraction is counterbalanced by vasorelaxing agents such as nitric oxide (NO), 15 which has been proposed as a regulator of sinusoidal blood flow in the normal liver.…”
Section: E Xperimental and Clinical Studies Have Indicated Thatmentioning
confidence: 99%
“…8,31 Briefly, after a combined digestion with collagenase/ pronase, HSCs were separated from other liver nonparenchymal cells by ultracentrifugation over gradients of stractan (Cellsep isotonic solution; Larex Inc., St. Paul, MN). Extensive characterization was performed as described previously.…”
Section: Isolation and Culture Of Human Hscsmentioning
confidence: 99%
See 2 more Smart Citations